Compilation and Analysis of Supply and Demand Management Scenarios of Iran's Energy System to Reduce Environmental Impacts Using LEAP - SHAKER MOHAMADI; ali emami meibodi; AMIRHOSEIN FAKEHI (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2019)
Today, in most countries, especially developing countries, economic growth is at the heart of planning. Since the place of economic activity is the environment, unfortunately, growth has had unfortunate consequences for the human environment. The main objective of this study is to measure the reduction of environmental pollutants and greenhouse gas emissions under policy-making scenarios compared to the reference scenario. The research method in this study is using the scenario analysis method based on Long Term Alternatives Planning Model (LEAP). The research findings show that by designing demand-side and supply-side management scenarios, meaning that replacing renewable energies and electricity in place of fossil fuels (crude oil and natural gas), reducing the amount of environmental pollutant emissions for the year 1420 (year horizon) 2014 (Year Zero Planning) is 123.5 million tonnes.